Application of multimedia in e-books system - Zeki, Akram M.; Ibrahim, Hazeeha; Senan, Shayma (IIUM Press, 2015)
In order to build effective online system, there is need to know the background of the problem. Because using traditional methods waste time, money, and energy. Wasting Time means; finding the person that have the book, finding the process that just convenient in day time, finding the person that want the book, time that is use to spread the message, and period of time for people to be aware of the handbill, poster, and pamphlet. Wasting Money means; cost of printing the handbill, poster, and pamphlet, the cost used to contact each other. Wasting Energy means; energy that is used in the process and the energy used to paste the handbill, poster, and pamphlet. E-commerce systems easily handle the process. E-commerce system can be explain as buying and selling products or services over electronic systems such as the Internet and other computer networks (Wikipedia, 2011). The book seller finder system is also one of e-commerce system. This chapter discusses an online-approach that can minimize the usage of three major things in our life; time, money, and energy. The main objective of this approach is to make the process of selling and buying books easy among International Islamic University (IIUM) community by replacing it gradually to online system. The Online Book Seller Finder system will be able to provide user with online buying, selling, and auctioning process. Online Book Seller Finder system will be able to benefit IIUM community to be more efficient when purchasing E-books.